Development of multifunctional textiles with mosquito repellent and antibacterial properties using microencapsulated lemongrass essential oil on cotton–polyester fabric - Johan, Nur Ain Arina; Hasmadi, Hannan Hamimi; Peter, Khatheline Shantie; Nasir, Siti Hana; Mustafa El Bakri, Helmy; Misni, Norashiqin (Korean Fiber Society, 2025)
This study presents an eco-friendly approach to developing multifunctional textiles by incorporating microencapsulated lemongrass essential oil (LEO) onto cotton–polyester blended fabrics. The treated fabrics were designed to exhibit mosquito repellent, antibacterial, and aromatic properties, offering a natural alternative to conventional synthetic finishes. LEO microcapsules were synthesized using the complex coacervation method and applied to the fabric via the pad-dry-cure method. The morphology of the microcapsules was analyzed using optical microscope, while the treated fabric was examined with scanning electron microscope (SEM). The functional performance of the treated fabric was evaluated through the arm-in-cage test, antibacterial assays, and sensory evaluation. Results showed that fabrics treated with 15% LEO microcapsules achieved 88% mosquito repellence efficacy protection before washing and 59% after 30 washing cycles, demonstrating durable functionality. The treated fabrics also maintained effective antibacterial activity and pleasant aroma retention. This study highlights a sustainable and eco-friendly finishing strategy for producing bio-functional textiles with potential applications in healthcare, outdoor wear, and wellness-related clothing.